Hope in view of HIV/AIDS in South Africa : public discourse, faith and the future - Olivier, Jill (University of Cape Town, 2014)
Do discourses of "hope" have real and practical consequences when it come to crucial issues such as policy, prevention, stigma, risk perception or funding? The following exploratory and treansdisciplinary study seeks to pull together a wide variety of the theoretical and analytical stances in order to examine the social construction of hope in the context of HIV/AIDS in South Africa. the theoretical framework is built from a base of cultural theory, discourse analysis and theology, and binds these together into a transdisciplinary argument.
Free
Keywords: HIV/AIDS and Society